Experimental Study on Deep Carburizing Process and Distortion Control of Large Modulus Rack - Li Baokui; Lu Jinsheng (Jixie chuandong)
Rack is the key component of the rotary device of the overweight roadheader. Its performance directly affects the bearing capacity, impact resistance and seismic resistance of the rotary device, which determines the safety, stability, reliability and service life of the roadheader. The deep carburizing and quenching technology, structure and distortion control technology of the 32 mm large modulus rotary rack in the rotary device of the roadheader are studied in combination with the performance requirements, structural characteristics and technical difficulties of heat treatment. The results show that, by the multi-stage carburizing process with high intensity carburizing and diffusion, the depth of the carburizing layer of the rack is up to 0.5 mm,the bending deformation of rack is 0.8~1.4 mm by process equipment and process control, and the metallographic structure are effectively controlled.